Management Program Implementation For Student Discipline Character Through Positive Value Habituation Program Management - Arif Nugraha; Irawan; Oman Warman; Oding Ahmad Effendy; Rizal Rahmatullah (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2023)
The research aims to investigate how Positive Value Habituation program management comprises planning, organizing, implementing, and monitoring. This research employed a descriptive analytic approach with a qualitative methodology. Observation, interviews, and documentation studies are utilized as methods of data collection. Based on data processing, the research results are as follows: Based on data processing, the research obtained are: (1) Program planning is carried out by means of a leadership work meeting to formulate and discuss what policies need to be applied in the program reference, program objectives to apply disciplined character, determine the schedule for a program, materials and determine the budget needed to carry out a program (2) Organizing is done by creating a school organizational structure for the division of tasks to staff to facilitate the program implementation process (3) Program implementation with routine, spontaneous, and programmed activities which are followed by students based on planned plans. has been determined. (4) Program supervision is carried out, namely to students by calling their parents, to personnel by giving rewards and